Characterization of the algC Gene Expression Pattern in the Multidrug Resistant Acinetobacter baumannii AIIMS 7 and Correlation with Biofilm Development on Abiotic Surface. (3rd December 2014) - Sahu, Praveen K.; Iyer, Pavithra S.; Barage, Sagar H.; Sonawane, Kailas D.; Chopade, Balu A.
Abstract : Relative quantification of algC gene expression was evaluated in the multidrug resistant strain Acinetobacter baumannii AIIMS 7 biofilm (3 to 96 h, on polystyrene surface) compared to the planktonic counterparts. Comparison revealed differential algC expression pattern with maximum 81.59-fold increase in biofilm cells versus 3.24-fold in planktonic cells (P < 0.05 ). Expression levels strongly correlated with specific biofilm stages (scale of 3 to 96 h), coinciding maximum at initial surface attachment stage (9 h) and biofilm maturation stage (48 h). Cloning, heterologous expression, and bioinformatics analyses indicated algC gene product as the bifunctional enzyme phosphomannomutase/phosphoglucomutase (PMM/PGM) of ∼53 kDa size, which augmented biofilms significantly in algC clones compared to controls (lacking algC gene), further localized by scanning electron microscopy. Moreover, molecular dynamics analysis on the three-dimensional structure of PMM/PGM (simulated up to 10 ns) revealed enzyme structure as stable and similar to that in P. aeruginosa (synthesis of alginate and lipopolysaccharide core) and involved in constitution of biofilm EPS (extracellular polymeric substances). Our observation on differential expression pattern of algC having strong correlation with important biofilm stages, scanning electron-microscopic evidence of biofilm augmentation taken together with predictive enzyme functions via molecular dynamic (MD) simulation, proposes a new basis of A. baumannii AIIMS 7 biofilm development on inanimate surfaces.